College Managers’ Views on The Employability of Vocational Engineering Graduates: A Case of The South African TVET College Sector - Nicolas Ndlovu; Micheal M van Wyk (STKIP Singkawang, 2023)
This study investigated the required competencies that TVET college engineering graduates need to be employable and become successful entrepreneurs after completing their studies. The study used a qualitative design and semi-structured interviews to collect the data. Purposive sampling was used to select the participants from three public TVET colleges in Gauteng. The study reported that National Certificate Vocational college engineering graduates need relevant engineering content knowledge, authentic practical engineering workplace experience, soft skills, technical skills and their application in the real world. It was also found that the engineering sector has a negative attitude towards TVET engineering graduates and that there is a lack of lecturers with engineering industry experience. We relied on a small sample; hence, the results of this study may not be generalisable, but moving forward, a cross-national study including all TVET programmes may be required; and, most probably, different results will be generated. We concluded by advocating the review of the TVET engineering curriculum and a paradigm shift to an intense formally supervised and examined industry-oriented workplace component that would boost the technical expertise of graduates. A widespread advocacy campaign in the engineering sector could also help to raise their awareness of TVET programmes.